119: Sleep Disorders Associated with Attention Problems in Adopted Children. Issue 6 (1st June 2014) - Rajaprakash, M; Kerr, E; Friedlander, B; Weiss, S
Abstract: BACKGROUND: Sleep problems occur in up to 25% of children and are more prevalent in children who have symptoms of inattention/hyperactivity as well as those who are insecurely attached to their caregivers. Studies show that foster children display sleep problems, but limited research exists on the prevalence and etiology of specific sleep disorders in adopted children. OBJECTIVES: To investigate the relationships between psychosocial factors and the incidence of sleep disorders in adopted children. DESIGN/METHODS: Participants were recruited through a notice sent to parents on an adoption council listserv and through discussion with families attending a social service meeting. Families were eligible to participate if their child was between two and seven years of age. Thirty parent questionnaires, measuring demographics, behavior, parent/child relationships, and sleep problems, were sent to families. Responses were analyzed using descriptive statistics and correlations. T-tests were used comparing children reported to be good vs. poor-sleepers. RESULTS: A total of 67% responded (n=20). Twelve children (60%) had sleep problems based on the Children's Sleep Habits Questionnaire. As compared to good-sleepers, those reporting sleep problems experienced more parasomnias (P<0.002) and trends to issues with sleep onset delay and sleep duration. Children with sleep disorders also had more attention problems (P<0.025), which correlated significantly with parental attachment scores (r=−0.69, P=0.01). CONCLUSIONS: Sleep disorders (especially parasomnias) were frequently reported in adopted children. Those reporting sleep disorders showed more attention problems, which were associated with lower levels of parental attachment. Further research in this area will help to develop targeted interventions to prevent sleep disorders in adopted children.